First-principles-based effective Hamiltonian simulations of bulks and films made of lead-free Ba(Zr, Ti)O3 relaxor ferroelectrics. (18th May 2015) - Prosandeev, Sergey; Wang, Dawei; Akbarzadeh, A R; Bellaiche, L
Abstract: A review of the recent development and application of a first-principles-derived effective Hamiltonian technique to the study of lead-free Ba(Zr, Ti)O3 (BZT) relaxor ferroelectrics is provided. In addition to the computation and analysis of macroscopic properties (such as different types of dielectric responses and electric polarization) and their connections to previous published works, particular emphasis is given to microscopic insights arising from this atomistic technique. These include (i) the numerically-found determination of the physical origin of the relaxor behavior in BZT; and (ii) the prediction of polar nanoregions and the evolution of their morphology as a response to temperature, electric fields and epitaxial misfit strain. Other striking phenomena that were predicted in BZT compounds, such as Fano resonance and field-driven percolation, are also documented and discussed. Finally, a brief perspective of possible remaining computational studies to be conducted in relaxor ferroelectrics, in order to further understand them, is attempted.